Reduction in caffeine withdrawal after open-label decaffeinated coffee. (February 2023) - Mills, Llewellyn; Lee, Jessica C.; Boakes, Robert; Colagiuri, Ben
Background: Withdrawal from addictive drugs can be reduced by administering placebo deceptively, but in the clinic it is unethical to deceive the patient. Open-label placebo effects have been observed across a range of psychophysiological phenomena, and may also apply to drug withdrawal. Method: 24-hour abstinent heavy coffee drinkers ( N  = 61) rated their caffeine withdrawal symptoms before being allocated to one of three groups. The Deceptive group was given decaffeinated coffee (decaf) and told it was caffeinated, the Open-Label group given decaf and told it was decaf and the Control group given water and told it was water. After 45 min, caffeine withdrawal was measured again. All participants rated their expectancies of withdrawal reduction from caffeinated coffee, decaf and water prior to being randomised and the end of the study. Results: There was a significant 9.5-point reduction in caffeine withdrawal in the Open-Label group (95% confidence interval (CI): 4.7, 14.3; p  = 0.002), which was 8.6 points less than the Deceptive group (95%CI: 0.4, 16.8; p  = 0.014) but 8.9 points greater than the Control group (95%CI: 0.6, 17.2; p  = 0.012). Pre-randomisation, participants expected caffeinated coffee to reduce their withdrawal symptoms the most, followed by water and decaf, Pre-randomisation expectancy of withdrawal was only associated with amount of withdrawal reduction in the Deceptive group. Conclusion: It appears as if open-label placebo caffeine (i.e. decaf) can reduce caffeine withdrawal symptoms, even when people do not hold a conscious expectancy it will do so. There may be ways to integrate open-label placebo procedures into clinical interventions for drug dependence without violating informed consent.